Behind the Essenes History and Ideology in the Dead Sea Scrolls - Davies, Philip R. (Brown Judaic Studies, 2020)
A collection of essays by Philip Davies on aspects of the Dead Sea Scrolls. While composed to stand along, together these essays create a strong synthetic argument about the Essenes and the production of the Dead Sea Scrolls that remains important and challenging to the present day.